Service quality as the source of competitive advantage in higher education: The difference between students´ expectations and perceptions - Renata Skýpalová; Helena Chládková; Chijioke Esogwa Nwachukwu; Hieu Minh Vu (Universidad de Deusto, 2024)
The aim of this paper is to measure and compare the quality of services provided by higher education institutions in the Czech Republic and Vietnam. It is not the sheer volume of services offered, but their quality, which matters as a strategic tool enhancing the competitiveness in the tertiary education market. Feedback from student-clients is valuable to school management in their efforts to improve the services supplied. Samples of hundreds of students from the Czech Republic and Vietnam were involved in the research applying the SERVQUAL method. The five-dimensional questionnaire was administered, and the obtained data were analysed using descriptive statistics and t-test. The results show that Czech respondents are less satisfied with the service quality than their Vietnamese counterparts. In both countries, the quality perception in all dimensions was lower than expectations, the largest gaps being found in the Assurance dimension. Czech students placed the greatest emphasis on the Empathy factor, while their Vietnamese colleagues preferred the Tangibles dimension. To improve the quality of services, higher education institutions in the Czech Republic are advised to facilitate fast and unambiguous information transfer, ensuring comfort, security, and a supportive learning environment for students, with helpful staff willing to address their concerns. Received: 3 January 2023 Accepted: 28 November 2023